Optimalisasi Peran HRD Dalam Meningkatkan Produktivitas Dan Profitabilitas Di PT Sentralsari Primasentosa - Kevira Eris Andini; Lia Nirawati (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the role of Human Resource Development (HRD) in enhancing productivity and profitability at PT Sentralsari Primasentosa. Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation reviews related to the company’s HRD policies and strategies. The results indicate that optimizing the role of HRD through technical training, strengthening interpersonal relationships, effective recruitment, and fostering a productive work culture significantly impacts employee productivity. Increased productivity contributes to operational efficiency and employee satisfaction, ultimately supporting the company's profitability. This study recommends strengthening sustainable training programs, implementing HR technology, and leadership development to ensure the company’s continued performance.